PEMATUHAN PRINSIP KESANTUNAN BERBAHASA DALAM WACANA POLITIK PADA MEDIA SOSIAL (KAJIAN SOSIOPRAGMATIK) - Musyawir, Musyawir (Journal of Innovation Research and Knowledge, 2024)
This study aims to explore and explain the form of compliance with the principle of politeness of language of netizens in discourse on social media Twitter, Facebook, and Instagram. This type of research is classified as qualitative research with a descriptive method. The main theory used to analyze the research data is the pragmatic theory, Geoffrey Leech on the principle of politeness of language. The data in this study are written data in the form of text (words or sentences) in the comments column of each political news post or upload. The data sources are obtained from political news uploads (political discourse) on social media Twitter, Facebook, and Instagram. This study focuses on the form of politeness of language. The data collection techniques used are observation techniques, documentation techniques, and note-taking techniques. Data analysis goes through four stages, namely data collection, data reduction, presentation and analysis of data, and conclusion/verification. The validity of the data is obtained through diligent observation, extended observation, peer examination and discussion, and triangulation. The results of the study indicate that there is compliance with the principle of single language and compliance with the principle of dual language. Compliance with the principles of politeness in a single language can be found in speech on Facebook social media, with one compliance with the principles of language politeness including compliance with the maxims of wisdom/wisdom, there are three (3) in speech data on Facebook social media. Meanwhile, compliance with the principles of dual language politeness can be found in speech on Twitter and Instagram social media with two compliance principles of language politeness at the same time including (1) compliance with the maxim of wisdom/wisdom with compliance with the maxim of agreement/compatibility found in speech data on Twitter social media, (2) compliance with the maxim of wisdom/wisdom with compliance with the maxim of praise found in speech data on Instagram social media.